KNOWLEDGE AND MISCONCEPTIONS OF PULMONARY TUBERCULOSIS PATIENTS AT DOTS CENTRE, URBAN MEERUT. - Bansal, R; Saleem, S; Goel, K; Kaur, G (Indian Journal of Community Health, 2013)
Background: India is the second most populated country in the world; it has more new TB cases annually than any other country. In 2008, 1.98 million were estimated to have occurred in India, of whom 0.87 million were infectious cases, thus amounting to a fifth of the global burden of TB.With the entire country geographically covered under the DOTS program, research into socioeconomic impact of TB on patients and their households is crucial for providing comprehensive patient-friendly TB services and to document the benefits of DOTS. Objective: The present study was undertaken with the following objectives: (1) To determine the socio-demographic variables of registered patients for DOTS Treatment at Urban Health Training center Meerut. (2) To assess knowledge, awareness and attitude regarding Pulmonary Tuberculosis and its treatment among the patients. Materials and Methods: A cross-sectional study of 200 TB patients was done using a pre-tested semi-quantitative questionnaire in UHTC Meerut Period of Study: During 2010-2012. Results: Knowledge and awareness regarding Pulmonary Tuberculosis in patients at DOTS centre, Urban Meerut was very poor. There is a great need to educate the people about misconceptions like food and utensils as mode of transmission. BCC using the person to person contact in community , at health center and awareness campaigns are crucial in educating the ignorance seen in our field practice area. Conclusion: Poor knowledge and misconceptions concerning tuberculosis was quite concern in the patients. TB control program will remain ineffective unless myths and fears of TB patients are addressed related to causation of tuberculosis, mode of spread, and methods of prevention.